Hubungan Perilaku Ibu Hamil Terhadap Pemanfaatan Pemeriksaan Triple Eliminasi di Puskesmas Kuala Bangka Kabupaten Labuhan Batu Utara Tahun 2022 - Leni Sinaga; Nur Azizah; Lidya Natalia Sinuhaji; Rosmani Sinaga; Deby Chuntya Yun; Marsa Adelia (NAJ Nursing Applied Journal, 2025)
Mother-to-child transmission of HIV, Syphilis, and Hepatitis B remains a public health challenge. Transmission can occur during pregnancy, childbirth, and breastfeeding. To reduce the rate of transmission, the Ministry of Health of the Republic of Indonesia launched the Triple Elimination program through screening pregnant women in integrated antenatal services. However, the use of this examination is influenced by the behavior of pregnant women, including knowledge, attitudes, and actions. To find out the relationship between the knowledge, attitudes, and actions of pregnant women with the use of Triple Elimination examinations at the Kuala Bangka Health Center, North Labuhan Batu Regency in 2022. This study is an analytical observational study with a cross sectional design. The sample consisted of 35 pregnant women who visited the Kuala Bangka Health Center. Data was collected through questionnaires and analyzed using the chi-square test. Most of the respondents had good knowledge (45.7%), positive attitudes (74.3%), and good actions (45.7%). There was a significant relationship between knowledge (p=0.007), attitudes (p=0.003), and actions (p=0.007) with the use of Triple Elimination examinations. Knowledge, attitudes, and actions of pregnant women have a significant relationship with the use of Triple Elimination examinations. Increased education and support in antenatal services is needed to support the success of the mother-to-child elimination program of HIV, Syphilis, and Hepatitis B.